Detection of antibody against newcastle disease virus in village chickens in Sri Aman division, Sarawak - Lawrence Jomiji, Guill Alvarez (Universiti Malaysia Sarawak (UNIMAS), 2003)
Newcastle disease is the main disease of village chickens in Malaysia. The present study attempted to detect antibody against Newcastle disease virus in Sri Aman Division. Enzyme-Linked immunosorbent assay detected 50 positive sera in 50 sera with antibody titres range from 1553 to 33329. An attempt to detect Newcastle disease virus by inoculation of test samples into II-day-old embryonated eggs and haemagglutination spot test found no virus in 44 tracheal and rectal swabs.